Meiotic instability in wheat cultivars genotypic effect, influence on fertility and selection of stable plants - Fernandes, Maria Irene B. de Moraes (Pesquisa Agropecuaria Brasileira, 2014)
A study concerning meiotic instability of wheat cultivars at "National Wheat Research, Center" of EMBRAPA was carried out. A high significant correlation value (r = 0.87**; P < 0.001) was found for pairing problems (univalents) in Cheyenne and Hadden wheats, when comparison on mother plants and the mean values of their progenies was made. For chromosomal breaks the value was non significant (r = 0.32), indicating higher genotypic influence on pairing. The differences in percentage of fertil flowers between selected progenies of meiotic stable and instable plants gave high significant X2 values for three cultivars. IAS 55. Londrina and Sonora 64, indicating the influence of chromosomal abnormalities on fertility of the next generation. The comparison between meteorological factors ten days before collection and cytological abnormalities showed lower but significant values for precipitation, temperature extremes, humidity and insolation indicating their influence on the meiotic behavior in a low scale. The Meiotic Index (percentage of normal pollen quartets) of 97 cultivars was also determined. 54% of the cultivars presented from 5% to 80% of plants with Meiotic Index below normality (less than 90). The significance of chromosomal abnormalities for plant breeding is also discussed.